Dry Powder Inhalers in the Digitalization Era: Current Status and Future Perspectives - Styliani Xiroudaki; Aurélie Schoubben; Stefano Giovagnoli; Dimitrios M. Rekkas (MDPI AG, 2021)
During the last decades, the term "drug delivery systems" (DDSs) has almost fully replaced previously used terms, such as "dosage forms", in an attempt to emphasize the importance of the drug carrier in ensuring the claimed safety and effectiveness of the product. However, particularly in the case of delivery devices, the term "system", which by definition implies a profound knowledge of each single part and their interactions, is not always fully justified when using the DDS term. Within this context, dry powder inhalers (DPIs), as systems to deliver drugs via inhalation to the lungs, require a deep understanding of the complex formulation-device-patient interplay. As of now and despite the progress made in particle engineering and devices design, DPIs' clinical performance is limited by variable patients' breathing patterns. To circumvent this pitfall, next-generation DPIs should ideally adapt to the different respiratory capacity of individuals across age, health conditions, and other related factors. In this context, the recent wave of digitalization in the health care and industrial sectors may drive DPI technology towards addressing a personalized device-formulation-patient liaison. In this review, evolving technologies are explored and analyzed to outline the progress made as well as the gaps to fill to align novel DPIs technologies with the systems theory approach.